WEB SERIES BEAUTY BESTIE SEBAGAI KAMPANYE DIGITAL BRAND EMINA COSMETIC - Elizabeth Dicy; Christina Tandaju (LPPM Universitas ARS, 2022)
The high internet penetration in Indonesia makes social media widely used by companies as an option to launch digital campaign activities. In order to launch a new series of products and increase awareness of the Emina Brigth Stuff Series, Emina Cosmetics launched a campaign activity entitled Beauty Bestie through Web Series shows that can be watched on Youtube. This study aims to find out how Web Series and You tube are used as campaign channels by Emina Cosmetic to campaign for the message of friends for the skin of teenagers in the midst of skincare awareness issues form an early age. This study uses a descriptive qualitative approach with a post positivistic paradigm, and uses the theory of Public Relations. The results found in this study are the Public Relations Campaign activities implemented by Emina Cosmetic using a persuasion strategy that is packaged in the form of a Web Series story that is broadcast on Youtube. This selesction of digital campaign channels is based on nine aspects of campaign channel selection and has succeeded in achieving communication goals and increasing brand awareness.